2021
DOI: 10.1002/ep.13752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diesel‐biodiesel‐alcohol blends on combustion, performance, and emission characteristics of a single cylinder compression ignition engine

Abstract: Synthesis of biodiesel from raw based waste materials is much more influential for economic support of the nation, as many researchers have concluded that the use of fossil fuels is no longer sufficient in the coming decade, so one should look into the alternate source of energy in order to sustain the energy for our daily needs. Neem methyl ester produced from waste neem seed, which is cheap, and available in the surroundings has an opportunity for nonconventional sustainable energy and whereas, rice wine alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This is the possible next target within the framework of ecology and sustainability of transport. Concentrations of 15 and 30% are commonly tested and reported in publications dealing with similar topics (Pradelle et al 2017;Devarajan et al 2022;Reang et al 2022). Furthermore, B15 and B30 is currently used in countries such as Indonesia or Brazil.…”
Section: Fuel Blend Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the possible next target within the framework of ecology and sustainability of transport. Concentrations of 15 and 30% are commonly tested and reported in publications dealing with similar topics (Pradelle et al 2017;Devarajan et al 2022;Reang et al 2022). Furthermore, B15 and B30 is currently used in countries such as Indonesia or Brazil.…”
Section: Fuel Blend Characterizationmentioning
confidence: 99%
“…According to Abed et al (2018) and Siva et al (2019), this phenomenon occurs because the calorific value of diesel fuel is higher than biodiesel. Reang et al (2022) tested diesel-biodiesel-rice wine alcohol and state that at full load D80B10RW10, D70B20RW10, and D60B30RW10 gives 1.46%, 2.86%, and 3.91% lower brake thermal efficiency (BTHE) than diesel used in single cylinder compression ignition engine. Datta and Mandal (2017) found that the BTHE and fuel efficiency of a compression ignition engine increases while using alcohol (methanol and ethanol) with biodiesel.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel fuel has a crucial problem related to exhaust, vibration, and acoustic emissions [7][8][9][10][11]. Biodiesel is considered an eco-friendly, bio-degradable, energy efficient, renewable, scientifically feasible, and non-toxic fuel alternative [12][13][14]. Besides, it is considered one of the safest fuels, because it has a high flash point amongst all conventional fuels [15], and can operate diesel engines with little or no adjustments [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lower C/H ratio and inherent oxygen content present in alcohols improve the degree of combustion 2,12 . Alcohol blends can also be used in engines without making major modifications to the fuel delivery system and combustion chamber, however, fuel additives may enhance the qualities of a fuel blend for blending higher fraction (more than 15%) to improve the mixing properties 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…2,12 Alcohol blends can also be used in engines without making major modifications to the fuel delivery system and combustion chamber, however, fuel additives may enhance the qualities of a fuel blend for blending higher fraction (more than 15%) to improve the mixing properties. 13,14 Alcohols have been tested by several researchers to understand the combustion behavior of a CI engine. Ning et al 2020 2 have studied combustion stability coefficient of variation (COV) and emission investigation for a CI engine operated under dual fuel mode where diesel was directly injected and varying substitutions of alcohol (methanol, ethanol and butanol; 0%-40% substitution at a step of 10%) were port injected.…”
mentioning
confidence: 99%